2012
DOI: 10.1007/s00464-012-2580-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic adrenalectomy in obese patients

Abstract: Our study did not show any difference in perioperative outcomes between RA and LA in obese patients. These results suggest that the difficulties in maintaining exposure and dissection in obese patients nullify the advantages of robotic articulating versus rigid laparoscopic instruments in adrenal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 13 publications
4
58
1
Order By: Relevance
“…The other significant outcome in favor of robotic surgery was the lower estimated blood loss, with a difference between groups reaching statistical significance (p = 0.001); seven of the nine studies reported less bleeding for robotics [14], [15], [16], [17], [18] and [19]. However, the detected difference of about 25 ml is not clinically relevant.…”
Section: Critical Analysismentioning
confidence: 98%
See 4 more Smart Citations
“…The other significant outcome in favor of robotic surgery was the lower estimated blood loss, with a difference between groups reaching statistical significance (p = 0.001); seven of the nine studies reported less bleeding for robotics [14], [15], [16], [17], [18] and [19]. However, the detected difference of about 25 ml is not clinically relevant.…”
Section: Critical Analysismentioning
confidence: 98%
“…Brunaud et al pointed out that the robotic approach offered advantages in obese patients as well and that they did not encounter any technical difficulty in their patients with a mean BMI of 30 kg/m2 (maximum of 44 kg/m2 in their series) [17]. In contrast, Aksoy et al reported no significant difference in perioperative outcomes between robot-assisted surgery and laparoscopy in obese patients undergoing adrenalectomy [16]. These authors experienced difficulty using the same robotic trocar configurations in obese patients due to the need for retraction of the spleen and liver compared with normal-weight individuals.…”
Section: Critical Analysismentioning
confidence: 99%
See 3 more Smart Citations